Wireless biomedical sensor networks: the technology - Freitas, Eduardo (2016)
The increase in research in the area of wireless sensor networks (WSN) has brought a whole new meaning to medical devices. This is mainly due to advances in microcontroller technologies. The WSN are cited as one of the major technologies of this century and hence it assumes importance in areas such as health, psychology, fire prevention, security and even the military. The great advantage of this technology is the ability to track, monitor, study, understand and act on a particular phenomenon or event. The primary purpose of a wireless health system is reliable data transfer with minimum delay. This work is a synthesis of vast research done as Wireless Biomedical Sensor Networks (WBSN), including experimental and non-experimental investigations as well as data from the theoretical and empirical literature which incorporates a wide range of purposes: definition of concepts, review theories and evidence analysis of methodological problems, seeking to generate a consistent and understandable overview of WBSN. Such systems are already being marketed, some are still under investigation. It is also the aim of this study to identify the characteristics of a WSN applied to health.